STUDENTS' PERSPECTIVES OF UTILIZING ENGLISH VIDEOS ON TIKTOK TO IMPROVE SPEAKING ABILITY AT THE ELEVENTH GRADE OF STATE SENIOR HIGH SCHOOL 11 PALEMBANG - Anisha Aprillia; Asti Veto Mortini; Ferri Hidayad (Esteem Journal of English Education Study Programme, 2024)
This research explores students' perspectives on the benefits of English videos on TikTok for improving speaking skills. Using a qualitative approach and case study method, data was collected through observation, questionnaires, and semi-structured interviews at SMA Negeri 11 Palembang. The findings indicate that TikTok videos significantly impact students' fluency in English. Observations revealed both strengths and weaknesses in school-based learning, while interviews with 20 respondents showed that watching English content on TikTok boosts students' confidence and speaking skills. 64% of respondents agreed that TikTok improves their speaking ability, while 34% sometimes felt it helped, and 2% disagreed. The study concludes that English videos on TikTok can be an effective tool for enhancing speaking fluency, though the level of impact varies among students.